Design and simulation of a rear underride protection device (RUPD) for heavy vehicles - Al-Bahash Z.F.; Ansari M.N.M.; Shah Q.H. (Taylor and Francis Ltd., 2023)
Accidents; Automobiles; Crashworthiness; Energy absorption; Mercury (metal); Transportation; Trucks; Design and simulation; Finite element simulations; Heavy vehicle; Passenger compartment; Performance analysis; Protection device; Test condition; Truck chassis; Finite element method